Die positivering van geborgenheid met die oog op ’n meer gedissiplineerde onderrig-leeromgewing - Oosthuizen, Izak (Koers, 2013)
Enhancing discipline in the learning and teaching environment by means of geborgenheit. Learner misconduct is a grave concern in South African education due to the negative effect it is having on teaching and learning. The approach in this argumentative and reflective article is one of deconstruction of constructs such as geborgenheit [secureness] and stronghold. The objective is to demonstrate how these concepts can be actualised to enhance a sound and orderly learning and teaching environment. An analysis shows that geborgenheit, which essentially entails protection and fostering, needs to be linked to, and actualised in the particular teaching and learning environment by activating an applicable geborgenheit-stronghold. For successful actualisation of the latter, it is crucial to unlock the applicable geborgenheit spaces for the enhancement of orderly teaching and learning in the classroom.